Resource Dependency and Sustainable Rural Development: The Role of Livelihoods and Regional Economic Potential in Berau, Indonesia - Endah Susanti; Endang Suprihatin; Dharma Yanti (Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the influence of rural livelihoods and regional economic potential on sustainable rural development through community empowerment and local economic development, as well as to examine the moderating role of resource dependency. The study was conducted in Berau Regency using a quantitative approach. Data were collected from village heads as key informants because they possess strategic knowledge regarding village development conditions, local economic potential, and community empowerment programs. The analysis method employed was Partial Least Squares Structural Equation Modeling using the SEM-PLS approach to test relationships among variables. The results indicate that rural livelihoods and regional economic potential have a positive and significant effect on community empowerment. Furthermore, community empowerment positively influences local economic development, while local economic development significantly contributes to sustainable rural development. The findings also reveal that resource dependency weakens the relationship between local economic development and sustainable rural development, indicating that excessive dependence on external resources may reduce community autonomy and sustainability capacity. This study contributes theoretically by integrating Resource-Based View Theory and Resource Dependence Theory in explaining sustainable rural development. Practically, the study provides strategic recommendations for local governments to strengthen community capacity, optimize local resources, and reduce dependency on external actors in rural development processes.